Comparación in vitro de la alteración dimensional del modelo definitivo según el tiempo de vaciado de la silicona por condensación - Ramírez Necochea, Dreyci Mildred (2014)
Materials and methods: 36 impressions were taken to a stainless steel model with condensation silicone Oranwash Zetaplus and divided into 3 groups according to the emptying time (0, 0.5 and 72 hours). To determine the dimensional alteration of the final models compared to the master model, 8 specific locations were measured with a specialized coordinate machine, model Contura G2 with ZEISS Scanning contact technology. Results: The non-parametric test of Wilcoxon was used for this study. It was found that only 6 of 8 locations had statistically significant differences: A, C, D, E, F y G. We found there´s more dimensional changes in models poured at 0 and 72 hours. However, it´s important to say that each location is independent from the other, each one with different values as shown in the master model, so that could be related to the fact that 2 of these 8 locations don’t have statistically significant results because in prosthetic works cause each of these locations is a critical point in the adaptation and cannot be taken as one. Conclusions: Despite of being a material with excellent reproduction properties, silicones condensation present bigger dimensional alteration when models are emptied long after taking the impression, which means the more time you wait to pour the models, the more dimensional alteration you will have. So, we can conclude that it´s recommended to make the casting with plaster 0.5 h after we´ve taken the impression because if we wait more time, we´ll find more distortion in the final design of the model, the same as if we pour them immediately, cause the impression material also needs time to recover elastically and be more stable.